1988
DOI: 10.1111/j.1744-7348.1988.tb03338.x
|View full text |Cite
|
Sign up to set email alerts
|

Apple replant disease: the influence of soil phosphorus and other factors on the growth responses of apple seedlings to soil fumigation with chloropicrin

Abstract: The effects of fumigating field soils before replanting apple are frequently predicted from bioassays where apple seedlings are grown in pots, some containing untreated soil and the others containing chloropicrin-fumigated soil. The results from 418 such bioassays made during eight years are discussed with reference to the effects of certain physical and chemical soil features.Soil phosphorus (P) content and pH had large effects on growth in fumigated (but not untreated) soils; they therefore had large effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…These may include, for instance, the use of selected micronutrients such as zinc while possibly excluding or at least very carefully operating with others like boron (Tukey et al, 1984). Adding mineral fertilizer, e.g., with P, (Sewell et al, 1988), as well as managing ground cover by adding compost or even biochar, may induce increased biocontrol properties of soils including a reduction of nematodes causing root lesions. Fertilization may thus affect ARD severity in nutrient-limited soils (van Schoor et al, 2009), but frequently failed to replace fumigation for replanting in temperate climates (St. Laurent et al, 2008;Mazzola and Manici, 2012;Glisczynski et al, 2016;Peruzzi et al, 2017).…”
Section: Soil Properties Affecting Ardmentioning
confidence: 99%
“…These may include, for instance, the use of selected micronutrients such as zinc while possibly excluding or at least very carefully operating with others like boron (Tukey et al, 1984). Adding mineral fertilizer, e.g., with P, (Sewell et al, 1988), as well as managing ground cover by adding compost or even biochar, may induce increased biocontrol properties of soils including a reduction of nematodes causing root lesions. Fertilization may thus affect ARD severity in nutrient-limited soils (van Schoor et al, 2009), but frequently failed to replace fumigation for replanting in temperate climates (St. Laurent et al, 2008;Mazzola and Manici, 2012;Glisczynski et al, 2016;Peruzzi et al, 2017).…”
Section: Soil Properties Affecting Ardmentioning
confidence: 99%
“…As far as we know, mycorrhizae-induced growth depression of apple tree has never been reported. Sewell et al (1988) conducted bioassays in which apple seedlings were grown in pots to predict the need of fumigation against apple replant disease. The results indicated that seedling height was generally greater when soil P availability was high in fumigated soils, but that in untreated soils it was mostly independent of P. This observation seems to suggest that, as mycorrhizal colonization is affected by soil P availability, mycorrhizal colonization with its potentially associated C drain is not involved in replant disease.…”
Section: Discussionmentioning
confidence: 99%
“…The original apple seedling bio-assay was based on methods recommended by Hoestra (1968) and the ADAS procedures were described in detail by Sewell et al (1988). Briefly, samples of soils to be replanted were divided into two parts; one was untreated and the other was partially sterilised by fumigation with chloropicrin.…”
Section: Methodsmentioning
confidence: 99%
“…This artefact of the seedling bio-assay, associated with the absence of vesicular-arbuscular (VA) mycorrhizal fungi after soil fumigation, was largely corrected by amending all soils with P before the tests. With P-amendment, the proportion of soils with economically significant growth responses increased from 39% (299 tests, 1976-81) to 67% (119 tests, 1982-84) (Sewell, Preece & Elsey, 1988). This paper considers further results from bio-assays made during 1985-88, additional effects of improvement in the assessment of plant growth, actual rather than proportional growth increases following soil fumigation, and effects of soil fumigation in relation to soil PH.…”
Section: Introductionmentioning
confidence: 98%